Factors associated with high cardiovascular risk in Putumayo - Jessica Paola Ruiz-Sandoval; Dayana Vizcaino-Sulbarán; Juan Pablo Alzate-Granados; Diana Isabel Cáceres-Rivera; Luis Alberto López-Romero (Revista Cuidarte)
Introduction: Sociodemographic factors such as geographic location are associated with high cardiovascular risk. Urban areas are characterized by densely populated areas with access to services, while rural areas have fewer people and limited services. Objective: To determine the factors associated with high cardiovascular risk according to the area of patients enrolled in a chronic care program in Putumayo. Materials and Methods: Analytical cross-sectional study. The population was selected through simple random sampling. Information on the main risk factors was collected and included in a multivariate logistic regression model. Results: A total of 1,190 patients were included (median age 59.5 years [IQR 53–66], 68.74% women). 86.22% of the patients had high cardiovascular risk, with a similar distribution between urban (87.95%, n=628) and rural (83.61%, n=398) areas and a statistically significant difference compared to low/moderate risk (p=0.033). The factors related to cardiovascular risk in this population were primary education (OR: 0.68, CI 95%: 0.38–1.24), secondary education (OR: 0.88, CI 95%: 0.42–1.83), higher education (OR: 0.33, CI 95%: 0.13–0.82), ethnicity (none) (OR: 2.13, CI 95%: 0.98–4.63), rural area (OR: 0.66, CI 95%: 0.47–0.94), and contributory health affiliation (OR: 6.58, CI 95%: 2.75–15.72). Discussion: This study revealed that factors such as education level, ethnicity, type of health affiliation, and area were related to cardiovascular risk. Conclusion: The results showed a high proportion of individuals with elevated cardiovascular risk in Putumayo, with statistically significant differences between areas.